Typology characterization of farmers in Africa RISING sites in Mali - Signorelli, S.; Azzarri, Carlo; Haile, Beliyou (International Institute of Tropical Agriculture, 2016)
This document presents a summary of a typology study done using quantitative statistical methods (discussed below) applied to micro data from the Mali Africa RISING Baseline Evaluation Survey (MARBES) (conducted in 2014) and secondary data on environmental/biophysical variables from various source. The quantitative approaches have the advantage that they are reproducible and do not impose any ex-ante structure to the clustering process, while more qualitative approaches can potentially incorporate less tangible insights such as cultural patterns. Once the different farm types are identified through systematic quantitative analysis, they need to be validated with input from Africa RISING colleagues (especially working in Mali).